2023
DOI: 10.3389/fncel.2023.1285836
|View full text |Cite
|
Sign up to set email alerts
|

Human motor neurons derived from induced pluripotent stem cells are susceptible to SARS-CoV-2 infection

Gioia Cappelletti,
Claudia Colombrita,
Fiona Limanaqi
et al.

Abstract: IntroductionCOVID-19 typically causes Q7 respiratory disorders, but a high proportion of patients also reports neurological and neuromuscular symptoms during and after SARSCoV-2 infection. Despite a number of studies documenting SARS-CoV-2 infection of various neuronal cell populations, the impact of SARS-CoV-2 exposure on motor neuronal cells specifically has not been investigated so far.MethodsThus, by using human iPSC-derived motor neurons (iPSC-MNs) we assessed: (i) the expression of SARS-CoV-2 main recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
(122 reference statements)
0
0
0
Order By: Relevance
“…However, although the neuroinvasive potential of SARS-CoV-2 was proposed at the outset of the pandemic ( L. Mao et al, 2020 ; Li et al, 2020 ; Moriguchi et al, 2020 ; Varatharaj et al, 2020 ), solid evidence to demonstrate neuronal infection in the human tissue remains in dispute. Several reports present compelling evidence of neuronal infection ( Paniz-Mondolfi et al, 2020 ; Ramani et al, 2020 ; Burks et al, 2021 ; de Melo et al, 2021 ; Meinhardt et al, 2021 ; Song et al, 2021 ; Cappelletti et al, 2023 ; Yang et al, 2024 ), while others reported no direct infection of neurons ( Brann et al, 2020 ; Pellegrini et al, 2020 ; Butowt et al, 2021 , 2023 ; Khan et al, 2021 ; Finlay et al, 2022 ; Zazhytska et al, 2022 ; Luczo et al, 2024 ). Similarly, studies in laboratory animals report both the presence ( Golden et al, 2020 , 2022 ; Oladunni et al, 2020 ; Zheng et al, 2021 ; Beckman et al, 2022 ; Olivarria et al, 2022 ; Seehusen et al, 2022 ; Vidal et al, 2022 ; Yu et al, 2022 ; Villadiego et al, 2023 ; Shimizu et al, 2024 ) and absence ( Bryche et al, 2020 ; Ye et al, 2021 ; Kishimoto-Urata et al, 2022 ; Verma et al, 2022 ) of neuronal infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the neuroinvasive potential of SARS-CoV-2 was proposed at the outset of the pandemic ( L. Mao et al, 2020 ; Li et al, 2020 ; Moriguchi et al, 2020 ; Varatharaj et al, 2020 ), solid evidence to demonstrate neuronal infection in the human tissue remains in dispute. Several reports present compelling evidence of neuronal infection ( Paniz-Mondolfi et al, 2020 ; Ramani et al, 2020 ; Burks et al, 2021 ; de Melo et al, 2021 ; Meinhardt et al, 2021 ; Song et al, 2021 ; Cappelletti et al, 2023 ; Yang et al, 2024 ), while others reported no direct infection of neurons ( Brann et al, 2020 ; Pellegrini et al, 2020 ; Butowt et al, 2021 , 2023 ; Khan et al, 2021 ; Finlay et al, 2022 ; Zazhytska et al, 2022 ; Luczo et al, 2024 ). Similarly, studies in laboratory animals report both the presence ( Golden et al, 2020 , 2022 ; Oladunni et al, 2020 ; Zheng et al, 2021 ; Beckman et al, 2022 ; Olivarria et al, 2022 ; Seehusen et al, 2022 ; Vidal et al, 2022 ; Yu et al, 2022 ; Villadiego et al, 2023 ; Shimizu et al, 2024 ) and absence ( Bryche et al, 2020 ; Ye et al, 2021 ; Kishimoto-Urata et al, 2022 ; Verma et al, 2022 ) of neuronal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this short treatment period also allowed for the rapid approval of drug trials due to the emergency, life-threatening COVID-19 pandemic conditions [13]. Similar approaches have also been considered for the development of drugs for the treatment of the severe acute respiratory syndrome and other life-threatening side effects of the virus, affecting other systems in addition to the respiratory system, such as the cardiovascular, gastrointestinal, nervous, immune and hematopoietic systems [20][21][22][23][24][25]. A different approach has been considered for the development of other drugs that are related to each of the different stages of COVID-19 and also for the "long COVID" side effects [11,[26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%